Front Cover: Improvement of Aglycone π‐Stacking Yields Nanomolar to Sub‐nanomolar FimH Antagonists (ChemMedChem 7/2019). (4th April 2019) - Schönemann, Wojciech; Cramer, Jonathan; Mühlethaler, Tobias; Fiege, Brigitte; Silbermann, Marleen; Rabbani, Said; Dätwyler, Philipp; Zihlmann, Pascal; Jakob, Roman P.; Sager, Christoph P.; Smieško, Martin; Schwardt, Oliver; et al.
Abstract : The Front Cover illustrates the adherence of uropathogenic E. coli to the bladder epithelium, depicting the initial step of a urinary tract infection (UTI). This adhesion is mediated by the adhesin FimH, located at the tip of type 1 pili of uropathogenic E. coli . Preventing this interaction of FimH with mannose epitopes present on the uroepithelial surface represents a promising strategy for an antiadhesive therapy of UTIs. Novel fluorinated biphenyl mannosides display nano‐ to subnanomolar affinity to all conformations of FimH relevant for disease progression. The high affinity of this new class of antagonists results from strong π–stacking interactions of the electron‐poor aglycone with the tyrosine gate of FimH. In combination with pharmacokinetic properties indicative of oral bioavailability, these compounds constitute promising leads for an antiadhesive treatment of UTI. More information can be found in the Full Paper by Beat Ernst et al. onpage 749 in Issue 7, 2019 (DOI:10.1002/cmdc.201900051 ).